Xenopsylla cheopis record as natural intermediate host of Hymenolepis diminuta in Lima, Peru - Gárate, Inés (2011)
In order to determine the role of rat fleas in the life cycle of Hymenolepis diminuta, between November 2009 and March 2010, 27 rats were captured in Cercado de Lima and their ectoparasites were examinated, using standard parasitological procedures. In examined rats, 22 (81.5%) were infected with the parasite H. diminuta, 85,2% were infested with siphonapters of the species Xenopsylla cheopis. Of the 158 fleas that were found, 12% housed cysticercoids in its hemocoel, which were inoculated into albino rats of Holtzman strain, and then developed to adult stage of Hymenolepis diminuta. The results of this study are conclusive and constitute the first record of the role of X. cheopis as natural intermediate host in Peru, making it necessary to reconsider the risk factors and preventive measures.